CALM, MAP, STRENGTHEN AND RESOLVE (C.M.S.R): A BRIEF INTERVENTION PROTOCOL FOR ANXIETY - Zago Neto, Paulo (Seven Editora, 2026)
The topic of anxiety has been widely studied in the field of science as a complex emotional response, involving physiological, cognitive and behavioral components (Barlow, 2002). Most traditional therapeutic approaches prioritize the symptomatic management of anxiety, where the majority only treat the effects of anxiety, but do not address, in a structured way, the generating cause, thus leaving aside the assumption that for there to be an effect, there must be a cause. This article intends to present an original therapeutic protocol, called “Calm, Map, Strengthen and Resolve” (A.M.F.R.), developed based on the literature in the area and based on the clinical practice of the author of this text. This therapeutic protocol model for combating anxiety is based on the assumption that anxiety is not a cause, but only an effect — where it presents itself as a sign that there are conflicts, real or imaginary, that need to be identified and resolved. The A.M.F.R protocol proposes four progressive steps, where the successor step depends on the predecessor step. The four steps are: CALM – MAP – STRENGTHEN – RESOLVE. The text was structured in order to explain what the aforementioned Protocol is, on what criteria it is organized and developed, in addition to presenting some practical cases that demonstrate its effectiveness and functionality. In short, we hope to contribute to publicizing this effectiveness, highlighting the advantages of applying and replicating the Protocol in other contexts, as it has proven to be a powerful resource for overcoming anxiety.DOI: https://doi.org/10.56238/sevened2026.014-001